PENGARUH DIGITALISASI SISTEM PERUSAHAAN DAN PENGELOLAAN PIUTANG TERHADAP EFEKTIVITAS ARUS KAS PADA PT.PNM (MEKAR) CABANG PADANG - Teguh Hidayat; Silmi Kaffah; Elsa Meirina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effect of digitalization of corporate systems and receivables management on cash flow effectiveness at PT. PNM (Mekaar) Padang Branch using a quantitative approach through multiple linear regression analysis. The research data were obtained from questionnaires distributed to respondents using a purposive sampling technique. The results of the study indicate that digitalization of corporate systems has a positive and significant effect on cash flow effectiveness, which means that the implementation of digital systems can improve efficiency, accuracy of recording, and accelerate financial management so that cash flow becomes more effective. Meanwhile, receivables management has a negative and insignificant effect on cash flow effectiveness, which indicates that there are still obstacles such as late payments and problem receivables so that it has not provided an optimal contribution to the smoothness of the company's cash flow